In Vitro Anthelmintic Evaluation of Acanthophora spicifera Macroalgal Extract Against Haemonchus contortus in Sheep - Sakti, A. A.; Kustantinah; Suwignyo, B.; Sofyan, A.; Panjono; Nurcahyo, R. W.; Baihaqi, Z. A.; Harahap, M. A.; Wulandari; Prasetyo (Faculty of Animal Science, IPB University, 2025)
This study investigated the chemical composition and anthelmintic activity of Acanthophora spicifera against Haemonchus contortus from sheep in vitro. Fresh macroalgae were collected from Sepanjang Beach, Gunungkidul, Indonesia. Proximate analysis, fiber fractions, mineral composition, and color profile analysis were conducted to determine chemical profile of the macroalga. It was extracted by maceration with 96% ethanol (1:5) and ultrasonication. Secondary metabolites analyzed from the extract included total flavonoids, phenols, tannins, and saponins. The anthelmintic activity was tested in vitro through H. contortus adult worm motility and egg hatch inhibition tests. Extract treatments included P0: 0.9% physiological NaCl (negative control); P1: 0.5 mg/mL macroalgal extract; P2: 1 mg/mL macroalgal extract; P3: 1.5 mg/mL macroalgal extract; and Palb: 0.5 mg/mL albendazole (positive control). Motility test results showed that the use of macroalgae at levels of 0.5, 1, and 1.5 mg/mL significantly reduced H. contortus motility (p<0.05). However, effective LD₅₀ was reached in 1 and 1.5 mg/mL within the first 10 hours, and LD₁₀₀ after 21 hours (p<0.05). None of the extract levels matched the efficacy of albendazole (p<0.05). The egg hatch inhibition test revealed that the use of macroalgae at levels of 0.5, 1, and 1.5 mg/mL significantly inhibited H. contortus egg hatching by more than 85.73% after 24 hours (p<0.01), demonstrating comparable efficacy to albendazole. Based on these findings, A. spicifera extract contains various secondary metabolites with anthelmintic activity, inhibiting both H. contortus adult worm motility and egg hatching. This suggests that A. spicifera has potential for further development as a bioanthelmintic for ruminant parasite control, although further in vivo studies are needed.